Audit of integrated communication in women’s fashion ventures in Nicaragua - González-Ros, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective is to evaluate the comprehensive communication of women's fashion enterprises in Nicaragua in order to identify strengths and communication needs. To this end, the questionnaire of the Integral Communication Audit Model (MACI) was applied to women entrepreneurs in the fashion sector belonging to the Nicaraguan Network of Women Entrepreneurs (REN). The results show strengths in most of the communication dimensions, mainly in organisational behaviour, dissemination of information, external relations and company image; but weaknesses in key aspects such as infrastructure, formation of working groups, and transmission of the company's financial information.